Framework for action : programme of United Nations activities and expected outcomes, 2008 - 2015 (UN New YorkUS, 2008)
Provides the overview of activities to be undertaken by a multiplicity of stakeholders at global, regional, national or local levels in the course of the multi-year campaign.
Keywords: VIOLENCE AGAINST WOMEN